Validation of a simple universal IELISA for the diagnosis of human brucellosis - Ayala, Sandra M. (2014)
Fil: Ayala, Sandra M. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.